IMPROVING STUDENTSâ SPEAKING SKILL THROUGH ROLE PLAY STRATEGY AT GRADE EIGHTH IN SMPN 6 RAMBAH - Dwiana, Ari Aprilia; Rahayu, Pipit; -, Eripuddin (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research was conducted to improve studentsâ speaking skill at eighth grade students of SMPN 6 Rambahthrough role play strategy used a Classroom Action Research (CAR) method which is conducted to solve thestudentsâ problem in English Speaking. The researcher did two cycles, which each cycle consists of planning, acting,observing, and reflecting. The qualitative data were gained by analyzing the field note and observation result andthe quantitative data were obtained from the studentsâ speaking score. The finding of this research indicated that theimplementation of role play strategy was successful since there is an improvement in students speaking skill. Thefinding showed an improvement in students speaking skill from the average of speaking test in cycle I was (56, 25)to (68, 62) the average of speaking skill in cycle II.